A Story of One Contest for the Post of Professor Rhetoric and Poetics of Vilnius University (Year 1809) - Markowska-Fulara, Helena (Slavistica Vilnensis, 2024)
The article delivers a reconstruction of the competition for the post of Professor of Rhetoric and Poetics announced at Vilnius University in 1809. The dispute between the then Rector of the University, Jan Śniadecki, and Professor Gotfryd Groddeck regarding the candidacy of Euzebiusz Słowacki unfolded in several phases. It began with opinions expressed about Słowacki even before the competition was announced and influenced its announcement. The most tumultuous course of events occurred during the sessions of the University Council in the first months of 1811, during which scholars discussed the paper submitted by Słowacki. Preserved records of the meetings and correspondence between professors and the curator of the district, Adam Jerzy Czartoryski, allow for a reconstruction of the course and nature of events, which provide an essential context for the literary ideas expressed in the writings of all participants in the dispute.